DNA barcoding of Thais species (Family: Muricidae) from west coast of India - Kumar, Ravi; Jaiswar, A. K.; Pavan Kumar, Annam; Chakraborthy, S. K.; Jahageerdhar, S. J.; Lakra, S. W. (Indian Journal of Fisheries, 2015)
Accurate species identification is essential for defining biological entities for sustainable management and conservation. Species identification under the genus Thais (Mollusca: Neogastropoda: Muricidae) based on shell morphology often mystify due to the phenotype plasticity. In this study, efficiency of DNA barcodes (mitochondrial cytochrome c oxidase subunit I gene – COI gene) was tested to discriminate six species of Thais from west coast of India. The COI gene analysis revealed that the average transitional pairs (Si =56) were less than transversional pairs (Sv=59) with an average ratio of 0.93. The mean intraspecific and interspecific distances were 0.09±0.011 and 0.19±0.012, respectively. The average between species distance was 2 times more than within species distance. However, the DNA barcodes were not able to discriminate all the species with high barcode gap. Further, intraspecific distance values were estimated by including reported sequences from other geographical locations to test the DNA barcode efficiency in delineating conspecific individuals across different geographical locations.